Search for a Higgs boson in the decay channel H -> ZZ((*)) -> q(q)over-barl(-)l(+) in pp collisions at root s=7 TeV - Chatrchyan, S. (2012)
A search for the standard model Higgs boson decaying into two Z bosons with subsequent decay into a final state containing two quark jets and two leptons, H -> ZZ((*)) -> q (q) over barl(-)l(+) is presented. Results are based on data corresponding to an integrated luminosity of 4.6 fb(-1) of proton-proton collisions at root s = 7TeV, collected with the CMS detector at the LHC. In order to discriminate between signal and background events, kinematic and topological quantities, including the angular spin correlations of the decay products, are employed. Events are further classified according to the probability of the jets to originate from quarks of light or heavy flavor or from gluons. No evidence for the Higgs boson is found, and upper limits on its production cross section are determined for a Higgs boson of mass between 130 and 600 GeV